“GST: Challenges In Implementation Of GST Rather Than VAT; Impact And Advantages Towards GDP Growth.” - et. al., Sunitha.G, (Turkish Journal of Computer and Mathematics Education (TURCOMAT), 2021)
GST stands for “Goods and Services Tax”, which is an ultimate destination for value added tax charged on the production, sale and consumption of goods and services. It includes all the indirect taxes of both state and central Governments and the total economy into a seamless nation in national market. GST consist of all Taxes which are charged indirectlyand this will help in development of economy and demonstrates to be more advantageous than the current tax system. GST will also support to quicken the total Gross Domestic Product (GDP) of the nation. The objective of the study is to analyze the influence of GST after its application. There is a need to study the differences between GST and current Indirect taxes, to know the advantages of GST, these are evaluated in the paper. The study briefly explains about the “challenges and advantages of GST after execution”. The significance of tax before and after the implementation of GST is described in the study. The consequent effects of it on general public is analyzed in the study. Descriptive sort of research is evaluated for the study. Secondary also as primary information has been gathered for the study.